2013
DOI: 10.1021/ma4012347
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Free-Radical Cross-Linking Polymerization: Comparative Experimental and Numerical Study

Abstract: Modeling free radical polymerization processes in the presence of cross-linkers is a challenging problem that has been addressed using numerous techniques for over more than half a century. However, a model providing a comprehensive description of the phenomenon has not been proposed yet. In this work, we implement a simple free-radical polymerization scheme of a monovinyl (difunctional) monomer and a divinyl (tetrafunctional) cross-linker in a Monte Carlo (MC) scheme, which describes polymer dynamics using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…The bacterial staining showed that the ROS was largely distinct from the bacteria and from features of the barnacle. We hypothesize that these ROS at the cuticle layers also contribute to oxidative crosslinking (Okay et al, 1995;Dijkgraaf et al, 2003;Lattuada et al, 2013), as seen in other crustaceans (Willis, 1999;Glazer et al, 2013), and are critical to cuticle development and hardening, as seen in insects (Hopkins and Kramer, 1992;Suderman et al, 2006;Andersen, 2010). Further work is needed to define the specific ROS present and show the extent of their presence during development as only post-metamorphic juveniles were examined.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial staining showed that the ROS was largely distinct from the bacteria and from features of the barnacle. We hypothesize that these ROS at the cuticle layers also contribute to oxidative crosslinking (Okay et al, 1995;Dijkgraaf et al, 2003;Lattuada et al, 2013), as seen in other crustaceans (Willis, 1999;Glazer et al, 2013), and are critical to cuticle development and hardening, as seen in insects (Hopkins and Kramer, 1992;Suderman et al, 2006;Andersen, 2010). Further work is needed to define the specific ROS present and show the extent of their presence during development as only post-metamorphic juveniles were examined.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the much more efficient 3D BFM method has been successfully used to describe the formation of percolating networks and the dynamics of polymer networks, with its predictions shown to compare well with experimental data. 21,22,[59][60][61][62][63][64][65][66] Moreover, BFM has been proven to be an efficient method to work with branched polymers, [67][68][69] …”
Section: A On-lattice Bfm Monte-carlo Methodsmentioning
confidence: 99%
“…Considerable effort has been devoted throughout the material science community to quantifying the polymerization process with the goal of predicting the final properties of the polymer network by combining simulations and experimental swelling data. 23 In spite of these efforts, a comprehensive description of the relationship between polymerization kinetics and final crosslink structure remains a challenging problem. The complexity of this problem is increased in the methacrylate-silorane hybrid formulations by variables such as polymerization-induced phase separation.…”
Section: Introductionmentioning
confidence: 99%